Use of Calendula officinalis in Wound Healing: An Overview (Revista Brasileira Multidisciplinar, 2024)
The history of medicinal plants is as long as the history of mankind. Medicinal plants are important sources of chemical substances that have beneficial therapeutic effects on human health. Calendula officinalis is a plant that has been used for centuries as a herbal medicine, especially in wound healing. The use of C. officinalis as a healing agent has already been supported by different in vivo and in vitro studies. Thus, the objective of this review is to provide an overview of current studies on the effect of Calendula on wound healing. The search for studies occurred in three databases, considering only studies from the last five years. This review included 03 in vitro studies, 04 in vivo studies in animal models and 04 clinical ones. Evidence suggests that C. officinalis may be an important source for the development of new effective healing drugs.